Variants in genes related to inflammation and endothelial function can increase the risk for carotid atherosclerosis in southwestern China - Xie, Yong; Yu, Ming; Qing, Ting; Luo, Hua; Shao, Minjie; Wei, Wei; Yi, Xingyang (Frontiers in Neurology, 2023)
Aim To investigate the potential association between polymorphisms in genes involved in endothelial function, inflammation and carotid atherosclerosis. Methods This was a three-center, population-based sectional survey conducted in Sichuan province of southwestern China. We randomly selected 8 different communities in Sichuan, and the residents in each community volunteered to participate in the survey by face-to-face questionnaire. A total of 2,377 residents with high stroke risk population in the 8 communities were included. Carotid atherosclerosis was evaluated by carotid ultrasound, and the 19 single nucleotide polymorphisms (SNPs) in 10 endothelial function as well as inflammation relevant genes were measured in the high stroke risk population. Carotid atherosclerosis was defined by the presence of carotid plaque or any carotid stenosis ≥15% or mean intima-media thickness (IMT) > 0.9 mm. Generalized multifactor dimensionality reduction (GMDR) approach was used to analyze gene–gene interactions among the 19 SNPs. Results Among the 2,377 subjects with high stroke risk, 1,028 subjects had carotid atherosclerosis (43.2%), of which 852 (35.8%) cases had carotid plaque, 295 (12.4%) cases had ≥15% carotid stenosis, whereas 445 (18.7%) had mean IMT > 0.9 mm. Multivariate logistic regression revealed that IL1A rs1609682 TT and HABP2 rs7923349 TT served as independent risk factors for carotid atherosclerosis (OR, 1.45, 95% CI: 1.034–2.032, p = 0.031, and OR, 1.829, 95% CI: 1.228–2.723, p = 0.003). GMDR analysis indicated that there was a significant gene–gene interaction found among IL1A rs1609682, ITGA2 rs1991013, and HABP2 rs7923349. After adjusting the covariates, the high-risk interactive genotypes in the 3 variants were significantly associated with a significantly higher risk for carotid atherosclerosis (OR, 2.08, 95% CI: 1.257–5.98, p < 0.001). Conclusion The prevalence of carotid atherosclerosis was observed to be extremely high in the high-risk stroke population in southwestern China. There were associations observed between the specific variants in inflammation and endothelial function relevant genes and carotid atherosclerosis. The high-risk interactive genotypes among IL1A rs1609682, ITGA2 rs1991013, and HABP2 rs7923349 significantly increased the risk of carotid atherosclerosis. These results are expected to provide novel strategies for the prevention of carotid atherosclerosis. The gene–gene interactive analysis used in this study may be very helpful to elucidate complex genetic risk factors for carotid atherosclerosis.